Genetic surfing, not allopatric divergence, explains spatial sorting of mitochondrial haplotypes in venomous coralsnakes. (1st July 2016) - Streicher, Jeffrey W.; McEntee, Jay P.; Drzich, Laura C.; Card, Daren C.; Schield, Drew R.; Smart, Utpal; Parkinson, Christopher L.; Jezkova, Tereza; Smith, Eric N.; Castoe, Todd A.
Abstract: Strong spatial sorting of genetic variation in contiguous populations is often explained by local adaptation or secondary contact following allopatric divergence. A third explanation, spatial sorting by stochastic effects of range expansion, has been considered less often though theoretical models suggest it should be widespread, if ephemeral. In a study designed to delimit species within a clade of venomous coralsnakes, we identified an unusual pattern within the Texas coral snake ( Micrurus tener ): strong spatial sorting of divergent mitochondrial (mtDNA) lineages over a portion of its range, but weak sorting of these lineages elsewhere. We tested three alternative hypotheses to explain this pattern—local adaptation, secondary contact following allopatric divergence, and range expansion. Collectively, near panmixia of nuclear DNA, the signal of range expansion associated sampling drift, expansion origins in the Gulf Coast of Mexico, and species distribution modeling suggest that the spatial sorting of divergent mtDNA lineages within M. tener has resulted from genetic surfing of standing mtDNA variation—not local adaptation or allopatric divergence. Our findings highlight the potential for the stochastic effects of recent range expansion to mislead estimations of population divergence made from mtDNA, which may be exacerbated in systems with low vagility, ancestral mtDNA polymorphism, and male‐biased dispersal.